Can Herbal Medicine Bridge the Gap in Smoking Cessation? A Review of Plant-Based Interventions for Nicotine Addiction (2021-2025) - Asri, Ebel Vigrajuska; Hartanti, Sarrah Ayu (International Journal Labs, 2025)
Tobacco use remains a significant global health challenge, with current cessation therapies often facing limitations in efficacy, accessibility, and side effects. This systematic review addresses the critical question: Can herbal medicine bridge this gap in smoking cessation by providing effective and affordable plant-based interventions for nicotine addiction? This review systematically synthesizes recent scientific literature from 2021 to 2025, gathered from major open-access databases, to identify and evaluate herbal interventions for nicotine dependence and withdrawal. Our findings delineate a diverse array of phytotherapeutic agents with promising multi-faceted pharmacological mechanisms. Piper nigrum and Acanthopanax koreanum demonstrated potential in mitigating withdrawal symptoms and normalizing neurological pathways associated with addiction. Piper sarmentosum and the combination of Cinnamon & Ginger exhibited protective effects against nicotine-induced oxidative stress, while Avena sativa improved quality of life and reduced stress, indirectly aiding cessation. Vernonia cinerea showed notable efficacy in increasing abstinence rates and reducing oxidative damage, comparable to conventional pharmacotherapy. However, evidence for Hypericum perforatum remained inconclusive, highlighting the need for more robust research. Overall, phytotherapy presents a compelling, accessible avenue for adjunctive smoking cessation therapy. Future studies must prioritize standardized clinical trials, dose optimization, and deeper elucidation of molecular mechanisms to fully validate their potential.